Tax Facilities through Omnibus Law Taxation: A Canon Taxation Review - Fidiana Fidiana (Policy & Governance Review, 2021)
This research is a conceptual study to examine tax policy in the pandemic situation with a canon taxation perspective, namely equity, certainty, convenience, and efficiency. The study conducted by using a literature review concerning the role of Omnibus Law includes tax facilities to attract foreign investment underlining strengths and weaknesses. Data is obtained through secondary sources in the form of archival reports and previous research relevant to the research. Based on the analysis of literature studies, this research produces several things. First, the principle of equity is found in adjusting corporate tax rates. Associated with the aim of attracting foreign investment, the tariff adjustment policy naturally will not be realized in 2020, where traffic between countries is restricted to prevent the spread of Covid-19. Second, in the tax policy scheme of domestic tax subject reclassification, which includes more than 183 foreigners working in Indonesia, and Indonesian citizens living abroad over 183 days are classified as subject to foreign tax. Tax is imposed on foreigners only on income earned in Indonesia. This pattern fulfills certainty principles. Third, the regional tax incentive scheme is an instrument that ensures the certainty of regional investment in line with the principles of equity and convenience. Furthermore, local tax exemptions can lower the price of consumer goods in the regions, thereby increasing the purchasing power of the wider community, which was hampered by the pandemic. In this way, local taxes play a role in increasing regional competitiveness through public policies (tax incentives), to improve the welfare of people, especially those affected by the epidemic. Fourth, the tax holiday scheme encourages industrial growth in accordance with the principle of efficiency.